ASSESSING THE EFFECTIVENESS OF IRRIGATED LAND USE IN THE AMUDARYA DISTRICT THROUGH DIGITAL TECHNOLOGIES (British Journal of Global Ecology and Sustainable Development, 2026)
This article highlights the importance and prospects of applying Geographic Information System (GIS) technologies in the rational and efficient use of land resources in the Amudarya district. The study analyzes the capabilities of GIS for the digitalization of land plots, monitoring processes, optimizing the placement of agricultural crops, and early detection of environmental problems.